Hidrólise enzimática e caracterização do concentrado proteico obtido da carne mecanicamente separada (CMS) de tilápia do Nilo (Oreochromis niloticus) - Mendes, Poliana dos Santos (2024)
Paraná is the leading state in Nile tilapia production. The filleting industry produces a significant number of by-products. One of the possibilities for using this solid waste is the production of mechanically separated meat (CMS), which is obtained from the separation of meat adhered to the fish carcass. Among the possible products to be obtained from these residues are protein hydrolysates, sources of essential amino acids with important functional properties, as well as the desired characteristics of the product can be controlled based on the selection of the enzyme and the conditions of this process. The objective of this study was to extract myofibrillar proteins from tilapia CMS, obtaining a protein concentrate (PC) with 65.94% proteins. This CP was hydrolyzed with the enzymes papain and alcalase defined from the Rotational Central Composite Design (DCCR), where time and enzyme concentration were the independent variables, and the dependent variables were degree of hydrolysis (GH), solubility, and emulsifying capacity. Fish protein hydrolysates (Fish protein hydrolysate, FHP) showed the highest GH for alcalase (GH 56.59 g/100g) in the FHP5 experiment with a concentration of the enzyme used of 0.3975% and hydrolysis time of 2.5 hours. For papain (GH 131.47 g/100g) it was at a concentration of 1.0% and a time of 4.0 hours. It can be observed that the papain enzyme presented higher GH in all experiments evaluated compared to alcalase. Regarding solubility, it was determined at pH values 5.0, 7.0, and 9.0, and it was observed that it was lower in experiments that had the activity of the papain enzyme in relation to the alcalase enzyme. Emulsifying properties were expressed as emulsifying activity index (EAI) and emulsion stability index (ESI). Results with the enzyme alcalase showed higher EAI in pH 5.0 and 9.0 conditions, while papain showed better results at pH 9.0. Better ESI values were observed for alcalase enzyme at pH 7.0 in experiment HPP3 (90.34 min), and for papain in experiment FHP6 (914.15 min) and FHP8 (909.95 min) at pH 7.0. The hydrolysis conditions are dependent on the profile of the desired product. In this study, the variables determined showed better results due to the action of the alcalase enzyme on FHP, mainly for solubility and emulsifying capacity. It was possible to determine a mathematical model with the desirability function considering the concentration and time for solubility and emulsifying capacity to optimize the hydrolysis process with alcalase at an enzyme concentration of 1.1025% and hydrolysis time of 4.615 hours. GH was observed higher for FHPC (20.59g/100g) compared to FHPO (13.80g/100g). Solubility was higher for FHPO compared to FHPC at pH 5.0 and 7.0; at pH 9.0, there were no significant differences. For ESI, higher values were identified for FHPO, the opposite happened for EAI, which presented higher values for FHPC. The HFP bands were characterized using FTIR analysis, which allows structural modifications and reductions in the protein chain to be evaluated qualitatively.